2010
DOI: 10.1177/0022034510384617
|View full text |Cite
|
Sign up to set email alerts
|

Modified Y-TZP Core Design Improves All-ceramic Crown Reliability

Abstract: This study tested the hypothesis that all-ceramic core-veneer system crown reliability is improved by modification of the core design. We modeled a tooth preparation by reducing the height of proximal walls by 1.5 mm and the occlusal surface by 2.0 mm. The CAD-based tooth preparation was replicated and positioned in a dental articulator for core and veneer fabrication. Standard (0.5 mm uniform thickness) and modified (2.5 mm height lingual and proximal cervical areas) core designs were produced, followed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 32 publications
6
80
1
8
Order By: Relevance
“…The fatigue of tested groups was not considered in this study. Certainly fatigue aspect is often the clinical phenomena particularly in aged restorations [26][27][28][29]. Further studies should investigate the aging of all-ceramic systems and compare the data with the findings of this study.…”
Section: Discussionmentioning
confidence: 54%
“…The fatigue of tested groups was not considered in this study. Certainly fatigue aspect is often the clinical phenomena particularly in aged restorations [26][27][28][29]. Further studies should investigate the aging of all-ceramic systems and compare the data with the findings of this study.…”
Section: Discussionmentioning
confidence: 54%
“…Before final maturation, a sample at "blue block" stage was sent for marginal fit evaluation. Final crowns were cemented to resin-based composite dies (Tetric EvoCeram, Ivoclar) and aged 30 days (Coelho et al, 2009a,b;Silva et al, 2010Silva et al, , 2011) with a self-curing resin-based dental luting material (Multilink Automix, Ivoclar) according to the manufacturer's instructions. These were then stored in water for a minimum of 7 days prior to mechanical testing.…”
Section: Methodsmentioning
confidence: 99%
“…Framework design modifications of porcelain fused to metal crowns have been suggested previously in an attempt to improve strength by providing support to veneering porcelain and also to improve esthetics without compromising strength. A recent study showed that framework design modifications on the lingual and proximal sides as lingual supporting structures increased the strength and support of veneering porcelain [27][28][29] . The zirconia-ceramic crown frameworks with lingual supporting structures are becoming more popular in clinical use 30) .…”
Section: Fracture Load Of Ce-tzp/amentioning
confidence: 99%